Discount Price Decisions in Attracting Buyer Interest in ASHAC&C SMEs in Jambi - Rosmita Rasyid; Levina Setiawan (CV. Proaksara Global Transeduka, 2025)
Price structure is one of the pricing strategies that is important in increasing consumer purchasing interest. Price is also the only part of the marketing mix that provides income for the company. The partner chosen in the PKM activity is a culinary business located in Jambi. PKM aims to assist partners in an effort to increase their knowledge ability in finding and understanding the right price structure in conducting business activities on the products sold. The method offered in this activity is training/socialization through zoom. The material is in the form of understanding the price structure which includes: understanding the price structure. The purpose of making discounts, factors that determine discount price decisions, factors that determine the structure of quality discounts. The importance of price structure in increasing purchase interest in partner products. Through this activity, it is hoped that the problems that arise in partner businesses will be resolved, partners can increase buyer interest by using the right discount price strategy. Outputs of PKM activities in the form of publications to national journals and HKI (Intellectual Property Rights).